Risk factors for severe hemorrhagic cystitis following BMT - Seber, Adriana [UNIFESP] (1999)
Hemorrhagic cystitis (HC) is a common toxicity of preparative regimens for bone marrow transplantation (BMT), Severe HC often requires prolonged and expensive hospitalization, and occasionally can result in death. To investigate the risk factors for severe HC, we conducted a retrospective study among 1908 patients who received BMTs at the University of Minnesota during 1974 to 1993, A previous report from our institution reported on 977 of these patients. We identified all patients with genitourinary complication within 100 days post-BMT from the BMT database. Medical charts for these patients were reviewed to determine whether the patient had HC and also the grade of HC, A total of 208 HC cases were identified during the study period. of them, 92 patients had severe HC, an incidence of 5% (95% CI = 4-6%), We found that grade II-IV graft-versus-host disease (RR = 2.56; 95% CI = 1.43-4.56), use of busulfan (RR = 2.69; 95% CI = 1.35-5.35), and age at transplant (RR = 2.20; 95% CI = 1.27-3.81, for age of 10-30 compared to age of 0-9) were related to an increased risk of HC. in contrast, transplant year was inversely associated with the risk of HC (trend test, P < 0.01). We did not find any significant difference in HC with the use of prophylactic Mesna.